REVOLUSI MENTAL DAN REVOLUSI ETOS KERJA: UPAYA MEMBANGUN BANGSA INDONESIA YANG LEBIH BERMARTABAT - DESMITA DESMITA (Ta'dib, 2015)
Mental revolution is a national movement and political jargon initiated by the Indonesian government nowadays. By using this jargon, it is expected that Indonesian people could achieve their dignity to be an independent, nobility, justice, and prosperous country. The mental revolution should be begun with job ethos – a mental attitude to see a job meaningfully. Job ethos is not seen as an effort to get salaries only. It is, however, an effort to do something meaningfully.  Job ethos will affect employee such as farmers, workers, merchants, and civil servant to do their jobs successfully and meaningfully.Kata kunci:  revolusi, mental, etos kerja